Enrique Foffani. Valllejo y el dinero. Formas de la subjetividad en la poesía. Lima: Editorial Cátedra Vallejo, 2018, 416 págs. - Espino Relucé, Gonzalo (2018)
He questions once again the ways in which critics have read the poetic production of our classic. This, undoubtedly, because his is based on Vallejo's loyalty in his labyrinth, the world Vallejo lived in and how this first-rate Latin Americanist reads modernity from his dissident condition and his humanism in the midst of the fury of capital.